Effect on Cardiovascular System by Hyperbaric Bupivacaine and Isobaric Ropivacaine Given By Sub-Arachnoid Block in Planned Lower Extremity Surgery - Muhammad Naeem Pasha; Sheeza Naeem Pasha; Ayeza Naeem; Syed Hurul Haque (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Objectives: Efficacy of two local anesthetic drugs such as Ropivacaine and Bupivacaine were compared when they were administered intrathecally during elective lower limb surgery. Furthermore, the side effects of both drugs were also studied in the similar research. Methods: The study was done double-blinded, un-biased and a randomized control trial. Cardiovascular system parameters such as average heart rate and average systolic blood pressure were monitored after medication given. Decreased BP, nausea, vomiting, shivering and headache were the parameters used to assess the side effects on the patients receiving both the drugs. Results: Action of these two drugs on cardiovascular system parameters were monitored and there was no valuable dissimilarity seen. No statistical significance was found in the duration of nausea, vomiting and headache. None of the patients reported bradycardia or backache. However, shivering was observed in the patients that were administered Bupivacaine as compared to Ropivacaine. Conclusion: Ropivacaine is a better drug of choice as compared to Bupivacaine while considering the hemodynamic parameters as well as the different post-operative symptoms. Clinical Trial Number: Reference number: 0031/14 (Authenticated by Ethical and Scientific Review Committee, Karachi Medical and Dental College)